THE DEMYSTIFICATION OF SNAKES IN EDUCATION: FROM IMMINENT DANGERS TO INTELLIGENT USES - da Costa Caetano, Rodrigo; Gitirana da Rocha, David; Dias da Silva, Wilmar (LINKSCIENCEPLACE, 2026)
Media and textbooks talk about snakes as death provokers. When poisonous, they cause ophidian accidents, which can lead to injuries, suffering, amputations, incapacity and death. They are stigmatized animals, and their importance for ecological balance is neglected. However, researches has revealed potential for improving the quality of human life through the pharmacology associated with venomics. Nevertheless, there is incipient reverberation in media, as well as an unsatisfactory insertion of the intelligent uses of snakes in High School, and difficulties to contemplate an extended perspective for the thematic in the Biology teaching formation. We propose a reflection based on scientific studies, data on ophidian accidents in Brazil and analysis of textbooks, aiming the articulation of knowledge and the popularization of research.